Behavioural finance: an exploratory review (Journal of Economic Research & Business Administration, 2022)
AbstractThe belief that investors care about utilitarian, rationality, cognitive errors and self-control characteristics by the traditional financial theories have been challenged in the literature over the years by the behavioural financial theories as being unrealistic. To the latter, investors are more often than not, subjected to self-deception, social influence, emotion and heuristic simplification decision-making biases in real life situations. Therefore, behavioural finance uses the influence of psychology to explain the behaviour of investors. For a better understanding of this approach, this paper presents an exploratory survey of the concepts and theoretical underpinnings in behavioural finance. It traces the foundational theories in financial decision and evolving behavioural finance theories. Our review brings to the fore the gap between traditional finance theories and real life situations which accommodates human aspects in decision making. Amidst the perceived several biases that may accompany human behaviour as it affects financial decisions, we conclude that both traditional and behavioural finance theories are essential for informed financial decisions.Keywords:  Covid-19, Behavioural Finance, Traditional Finance, Financial Decision,, Exploratory Survey.